PENGGUNAAN SMARTPHONE DALAM INTERAKSI SOSIAL MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS SAHID SURAKARTA - Rheza Ardianto; Bedjo Sukarno, Dian Esti Nurati (Solidaritas, 2017)
PENGGUNAAN SMARTPHONE DALAM INTERAKSI SOSIAL MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS SAHID SURAKARTA Oleh:Rheza ArdiantoBedjo SukarnoDian Esti Nurati ABSTRACTThe presence of communication technology in the form of beneficial activities for smartphone social interaction becomes quick and easy, although remotely, through voice or text (writing). The purpose of this research is to analyze the use of smartphones in the matter of social interaction between students of the University, the Faculty of communication sciences Sahid. The theory used is the theory of social interaction from Soerjono Soekamto.Research methods used descriptive qualitative approach, using different types of data used the primary data and secondary data. The technique of determination of the informants using purposive sampling, data collection is done with the interview and documentation. As for the data analysis technique used to use descriptive qualitative analysis.Based on the research results obtained form the conclusion that the interactions that take place between students tend towards the associative, i.e. students utilize a smartphone to do cooperation with other students by forming groups on the application of chat and social media. The main purpose of the creation of this group is to spread information about the lectures, complete tasks and associated costs. Smartphone can make it easier to get information. Smartphone users, it will make it easier to get information more quickly, and can share and access information anywhere. Can communicate worldwide, that has smartphone, easily able to communicate with people in different parts of the world. Can chat and video call with different people and countries with people nearby. The use of the smartphone makes it easy to send email and find the place packed with a use application Zomato, Uber Eats, Restaurant Finder, and others. Keywords: Smartphone, Social Interaction, Student